A 3-DOF quick-action parallel manipulator based on four linkage mechanisms with high-speed cam. (September 2017) - Wu, Jing; Yan, Rui-Jun; Shin, Kyoo-Sik; Han, Chang-Soo; Chen, I-Ming
Highlights: A high-speed cam based on a 7th polynomial curve is designed, which is optimized by using NURBS curve. A quick-action linkage mechanism based on the high-speed cam is proposed, which has two movement phases, a fast-out phase and a slow-back phase. A 1T2R quick-action parallel manipulator is developed by arranging four proposed linkage mechanism in a way of quadrantal symmetry. The kinematic and dynamic analysis for both the quick-action linkage mechanism and 1T2R parallel manipulator are presented, and their movements are validated with simulations. Abstract: Quick-action mechanisms are always favoured in industrial applications because of its high efficiency. To pursue the high stiffness, low inertia and large payload capacity of the quick-action mechanism, this paper proposes a 1T2R 3-DOF quick-action parallel manipulator, which is developed based on four linkage mechanisms with high-speed cam. The cam is designed by using a 7th degree polynomial curve having high-speed motion. Based on this cam, a quick action linkage mechanism is proposed to realize a fast-out and a slow-back motion. Then kinematics and static forces of this linkage mechanism during the motions are analyzed, and its corresponding dynamics model is constructed. By arranging four linkage mechanisms in a way of quadrantal symmetry, a quick action parallel manipulator is capable of realizing three types of movements. Position and first-order kinematics of this manipulator are analyzed to illustrate its motion characteristics. Finally, the quick action linkage mechanism is validated by simulating a fixed trajectory of the end-effector in both two phases, and the parallel manipulator is validated by showing the simulation results of its output actions and the joint parameters during the movements. These analysis and validations show that both the proposed linkage mechanism and the 1T2R parallel manipulator have quite a few potential applications to enhance production efficiency and save energy.